2014
DOI: 10.1371/journal.pone.0108219
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malformations among Babies Born Following Letrozole or Clomiphene for Infertility Treatment

Abstract: ContextClomiphene citrate (CC) is the first line drug for ovulation induction but because of its peripheral antiestrogenic effect, letrozole was introduced as the 2nd line drug. It lacks the peripheral antiestrogenic effect and is associated with similar or even higher pregnancy rates. Since letrozole is a drug for breast cancer, its use for the purpose of ovulation induction became controversial in the light of studies indicating an increased incidence of congenital malformations.AimsTo evaluate and compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 22 publications
1
35
1
5
Order By: Relevance
“…After reading the 25 remaining articles, 12 were excluded. Table S1 summarises the excluded studies and the reasons for exclusion from the final meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the 25 remaining articles, 12 were excluded. Table S1 summarises the excluded studies and the reasons for exclusion from the final meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Table S1 summarises the excluded studies and the reasons for exclusion from the final meta-analysis. [14][15][16][17][18][19][20][21][22][23][24][25]…”
Section: Data Source and Selectionmentioning
confidence: 99%
“…Even though some associations between CC use and various types of birth defects and malignancies were observed [37] , there is no conclusive evidence that CC treatment increases the risk of birth defects [10] . Letrozole was initially associated with an increased rate of cardiac and bones anomalies [38] , but many subsequent studies have since confirmed its safety [24,[39][40][41] . Most comparative studies now confirm that the anomaly rates with CC and letrozole are comparable and similar to the rates in a population of healthy women who conceive naturally [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Hayvan modellerinde yapılmış bir çalışmada letrozolün teratojenik etkisi olduğu bildirilmiş olmasına rağmen, daha sonrasında letrozolun konjenital anomali riskinde artışa yol açtığı gösterilememiş-tir. 24 …”
Section: Aromataz İnhi̇bi̇törleri̇unclassified